The Profile of Junior High School Students' Satisfactions through Online Learning Integrated Science Subjects in the Covid-19 Pandemic Period - Afifah, Saidatul; Parmin, Parmin (Universitas Negeri Semarang, 2022)
The emergence of the corona virus outbreak to various parts of the world requires learning in Indonesia to be carried out online. The new learning system has obstacles in its implementation. This study aims to determine the level of student satisfaction with integrated science learning online. The type of research used in this research is descriptive quantitative and qualitative conducted by survey method by providing scale and interviews. The data collection technique was done by purposive sampling method. The subjects in this study were students of class VIII and IX SMP NU Suruh with the slovin formula obtained a sample of 48 students. Test the validity of the instrument using the content validity test by the supervisor. The data obtained from the questionnaire results were analyzed using descriptive percentage analysis techniques, while the interview data were processed using the Miles and Huberman analysis technique which consisted of three stages, namely data reduction, data presentation, and conclusion drawing and verification. The results showed that in general the level of student satisfaction with integrated science learning online was in the high category.